Web Search as a Linguistic Tool - Fourney, Adam; Morris, Meredith Ringel; White, Ryen W. (Proceedings of WWW 2017, 2017)
Many people rely on web search engines to check the spelling or grammatical correctness of input phrases. For example, one might search [recurring or reoccurring] to decide between these similar words. While language-related queries are common, they have low click-through rates, lack a strong intent signal, and are generally challenging to study. Perhaps for these reasons, they have yet to be characterized in the literature. In this paper we report the results of two surveys that investigate how, when, and why people use web search to support low-level, language-related tasks. The first survey was distributed by email, and asked participants to reflect on a recent search task. The second survey was embedded directly in search result pages, and captured information about searchers' intents in-situ. Our analysis confirms that language-related search tasks are indeed common, accounting for at least 2.7% of all queries posed by our respondents. Survey responses also reveal: (1) the range of language-related tasks people perform with search, (2) the contexts in which these tasks arise, and (3), the reasons why people elect to use web search rather than relying on traditional proofing tools (e.g., spelling and grammar checkers).